Cardiorespiratory and Neuromuscular Responses during Water Aerobics Exercise Performed with and without Equipment - Pinto, S. S.; Cadore, E. L.; Alberton, C. L.; Silva, E. M.; Kanitz, A. C.; Tartaruga, M. P.; Kruel, L.F. M. (International Journal of Sports Medicine, 2011)
The aim of the study was to compare the cardiorespiratory and neuromuscular responses to water aerobics exercise performed with and without equipment. 15 women performed stationary jogging combined with elbow flexion/extension without equipment, with water-drag forces equipment and with water-floating equipment, at 2 submaximal cadences and at maximal cadence. Heart rate, oxygen uptake and electromyographic signal from biceps brachii, triceps brachii, biceps femoris and rectus femoris were collected during the exercise. The heart rate and oxygen uptake showed significantly higher values during the execution of the water aerobics exercise with either equipment compared to the execution without equipment. In addition, significant difference was found between submaximal cadences. For neuromuscular responses, no significant differences were found between the submaximal cadences for all muscles analyzed; however, significant differences were found between these submaximal cadences and the maximal cadence. Similarly, the results showed no significant differences between the execution of the exercise with or without equipment, except in the muscle activation of triceps brachii and biceps femoris, which was higher when using water-floating and water-drag forces equipment, respectively. In conclusion, the water aerobics exercise presented higher cardiorespiratory responses with equipment and also increased the cadence of execution. Nevertheless, neuromuscular responses were higher only at maximal cadence.
Keywords: oxygen uptake; heart rate; muscle activation; water-based exercise; equipment